Growth performance and blood profile of female rabbits fed dietary Cerium Oxide (Journal of Bio-Science, 2015)
Context: Rare earth elements, the 15 lanthanide elements with atomic numbers 57 (lanthanum) through 71 (lutetium), have been reported to be capable of producing reasonable growth-promoting effects in all classes of livestock and at the same time increase milk yield and egg production. However, concentration and type of rare earth element as well as the compositions of individual elements are important factors influencing the performance enhancing effects of REE on animals. Objective: The effects of inclusion of different dietary concentrations of Cerium oxide (CeO), a Rare Earth Element on growth performance and blood parameters of female rabbits. Materials and Methods: In an 8-week feeding experiment, 32 growing female rabbits were used. The rabbits were assigned to different dietary concentrations of Cerium oxide (CeO) at 0, 100, 200 and 300 ppm. The initial weight, feed intake and final weight were determined. Blood samples were collected on the last day of the experiment for hematological and serum biochemical analyses. Results: The daily weight gain, daily dry matter intake and feed conversion ratio significantly increased (P